Love in the Works of Claire Martin - Abrioux, Lewese Ann (My University, 1973)
It is my intention within this thesis to analyse the conception of love which Claire Martin presents in her works. This conception of love, based on the author's own childhood experiences, has as its central idea the emancipation of women. Claire Martin delves directly into the minds of her characters, revealing to the reader their innermost thoughts. The universe which she creates, however, is a particularly negative one, viewed almost exclusively from the perspective of a past love which has been eroded by time. Her novels propose no revolutionary outlook or ethic of love - their value lies in the analytical study which they offer into the very minds of characters influenced by the force of love. It is the aim of my thesis, therefore, to reveal rather than to explain this picture of love.
Keywords: Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures